THE USE OF CEMENT PAPER IN THE CREATION OF BANYUMAS STYLE WAYANG PURWA PUPPETS FOR THE STORY OF GATOTKACA'S BIRTH - Supena, Jimmy Supena (Arty: Jurnal Seni Rupa, 2025)
The study project entitled “Utilization of Cement Paper in Making Wayang Purwa Gagrag Banyumas in the Gatotkaca Born Story” aims to introduce to the public that alternative materials for making puppets can utilize cement paper and introduce one of the stories in the puppet character Raden Gatotkaca. The form of wayang with Banyumas gagrag which is rarely used in wayang performances is one of the efforts to preserve the Banyumas gagrag. The author took the initiative to visualize the portrait of the character in the Gatotkaca Lahir story in the wayang purwa artwork. In visualizing the subject, the author focuses on the form of puppets that are specially made using tatah and sungging techniques. The author chooses to utilize alternative cement paper waste as a form of environmental conservation. Twelve works are presented with titles including: Raden Werkudara, Dewi Arimbi, Jabang Tetuka, Dewi Suprobo, Sang Hyang Manikmaya, Sang Hyang Narada, Sang Hyang Indra, Sang Hyang Bromo, Raden Gatotkaca, Kresna, Naga Pracona, Patih Sekipu.